Stochastic Flowshop Scheduling Model for Two Machines - Tyagi, Neelam; Tripathi, R. P.; Chandramoul, A. B. (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*302.81px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.0141);" role="presentation">In this paper, we have developed a new heuristic algorithm for n <span dir="ltr" style="left: calc(var(--scale-factor)*364.63px); top: calc(var(--scale-factor)*302.81px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.972905);" role="presentation">jobs two machines (<span dir="ltr" style="left: calc(var(--scale-factor)*453.94px); top: calc(var(--scale-factor)*302.81px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00123);" role="presentation">